Recovering 9/11 in New York - Fanuzzi, Robert; Wolfe, Michael (Cambridge Scholars Pub, 2014)
This collection of essays offers a rich variety of approaches to how people and institutions in greater New York have sought to find meaning in the 9/11 attacks on the World Trade Center, now a decade on. The views and practices documented here join memory, recovery, and rebuilding together to form a vital new chapter in New York's metropolitan history. Contributors contest the dominant nationalist narrative about 9/11 to generate a more local and socially-engaged form of scholarship that co ...